Systematic monitoring in forming the availability of future geography teachersfor core (profile) education high school students as a necessary condition for the effectiveness of this process - Мантуленко, Світлана (Pedagogy of Higher and Secondary Education, 2014)
Mantulenko S. V. Systematic monitoring in forming the availability of future geography teachersfor core (profile) education high school students as a necessary condition for the effectiveness of this process. The analysis of scientific approaches for the determination the problem of monitoring in education, the theoretical justification of the systematic monitoring in forming the availability of future geography teachers for core (profile) education high school students as a necessary condition for the effectiveness of this process are realized in the article.